Analisis Cemaran Staphylococcus aureus pada Saus yang digunakan Pedagang Bakso di Lingkungan Sekolah Dasar Kecamatan Banda Sakti Lhokseumawe - Putri Athira Tarigan; Mardiati Mardiati; Juwita Sahputri (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Sauce is a processed product made from fruits or vegetables in paste form and is commonly used as a food condiment, especially in popular street foods like meatballs (bakso) in Indonesia. Inadequate attention to hygiene and sanitation in food handling can lead to contamination by microorganisms, including Staphylococcus aureus. This study aimed to evaluate the hygiene and sanitation practices of meatball street vendors around elementary schools in Banda Sakti District, Lhokseumawe, and to detect the presence of S. aureus contamination in the sauces used, as well as assess compliance with the Indonesian National Standard (SNI) 7388-2009. The research involved interviews and observational assessments of vendors, as well as laboratory analysis of 25 sauce samples using the Spread Plate method on Baird Parker Agar with three levels of dilution and colony counting based on the Aerobic Plate Count formula. Samples were collected using purposive sampling. The results showed that vendors had good hygiene and sanitation practices, and no S. aureus contamination was found in the sauce samples. Therefore, the sauces met the microbial safety standards set by SNI 7388-2009. In conclusion, the vendors maintained proper hygiene and sanitation, and the sauces used were free from Staphylococcus aureus contamination, indicating compliance with food safety standards.